Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

find y for the linear equations 2x-3y=6 and find y for -10x=5y

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer

SIGN UP FOR FREE
duno
rearrange for y. 1) 2x-3y=6 2x -6 = 3y 2/3x-6/3 = y y=2/3x -2 2) -10x = 5y try this one yourself.
ok wannabeagirl then go away

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

\[gj\]
retriceole
@jayds i got for 1 x-1.3
i really don t under stand
find y means that you have to isolate y, do you see how I did it above? we want y = ............... Lets use an example say 5x + y = 9 I want to find "x" this time not y, so I just bring the y to the right hand side and bring the 9 to the left hand side. 5x - 9 = -y y = -5x + 9 do you understand?
so if i put -1 in the place of x what will it be
sorry, I do not understand what you are trying to say.
so instead of y=2/3x -2 what will it equal if \[ y=2/3\times-1 -2\]
you know what im saying
ok, substitution of x=-1 inside the equation is what u mean. then you just solve it. y=2/3 x -1 -2 y= -2/3 -2 y=-3.667
okkkkkkkkkkkk now i understand thanks so much!
it's ok, medal thanks :P

Not the answer you are looking for?

Search for more explanations.

Ask your own question